The Role of ICT Regulations in Agribusiness and Rural Development - Kayumova, Marina (World Bank, Washington, DC, 2017)
Agriculture plays a vital role in the development of many countries. Access to markets, finance and information are cornerstones for agricultural growth. Information and Communication Technology (ICT) supports farmers by facilitating access to markets through real-time data on market prices, weather forecasts, information on pests, seed varieties and planting techniques. A major impediment for smallholder farmers to fully exploit the benefits of ICT is the lack of sufficient infrastructure and mobile networks in rural areas. A reason for this persisting network coverage gap stems from the significant capital investments required for providing widespread ICT access, which mobile operators have often little incentive to make since the potential profit margins in rural areas are relatively low. This paper examines the role of regulations in facilitating ICT access and ultimately rural development. The remainder of this paper is organized as follows. The second section discusses the role of an enabling environment and ICT regulations that are critical for expanding access to rural areas. The third section presents the new data set on the quality of regulations followed by the analysis of the relationship between regulations and key ICT development indicators. The final section draws some concluding remarks.